Comparison of Outcome Between Long Posterior Burgess Flap and Skew Flap in Below Knee Amputation in Diabetics - Zafar, Muhammad Asad; Ashraf, Imran; Fatima, Sidra; Minhas, Farooq Sultan; Zahid, Rashid; Naveed, Qaisar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate and compare the results between the long posterior Burgess flap and skew flap surgical approach in below knee amputations among diabetic patients and to determine which approach produces better outcomes in terms of mobility, mortality rate, revision status, hospital stay, follow-up, limb fitted, and wound healing. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Surgery, Combined Military Hospital, Kharian, Pakistan, from Jul 2021 to Jul 2023. Methods: This quasi-experimental study was conducted on 60 patients undergoing below-knee amputation, comparing skew flap and Burgess flap techniques. Outcomes including mobility, wound healing, and hospital stay were analyzed with independent sample t-tests using SPSS v26 where a p-value of ≤0.05 was considered as significant. Results: Mean age of participants was 60.38±5.88 years. Wound exudate was noted in 2(7%) patients in Burgess flap and 6(20%) in skew flap while major flap necrosis was observed in 10(33%) patients with Burgess flap and 17(56%) patients with skew flap, 16(54%) patients with Burgess flap completed follow-up after 6 months while 18(60%) patients in skew flap group did. A further 20 patients died (8 in Burgess flap and 12 in skew flap) during the follow-up period,15 patients were immobile (50%), 8 patients were dependent (26%) and 7 patients were independent (24%). By comparing the two groups’ outcomes, there was significant difference noted. Conclusion: This study suggests that the long posterior Burgess flap technique may be a more favorable choice for below knee amputation among patients with diabetes mellitus.